MARKETING MARGIN OF LOCALLY PRODUCED MILK COWS IN THE PROVINCE OF BAGHDAD/DISTRICT ABU- GHRAIB FOR PRODUCTIVE SEASON 2015 - & AHMAD, HUSSAN (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This research aim to marketing margin account of one kg milk cows to the province of Baghdad district of Abu Ghraib. Collected a sample of (146) producer cow’s milk, (15) broker (milk collector's) and (21) retailer, random sample selection manner. The average marketing margin of one kg milk cows was about 400 dinars \ kg, marketing margin retailer and broker were about (250,150) dinar\ kg respectively, marketing costs of the retailer and broker have amounted to (81.42, 22.02) dinar \ kg. Retailer and broker profits amounted to about (168.58, 127.98) dinar \ kg. Dinar per consumer paid all of the producer , retailer and broker was amounted to (46.7, 33.3, 20.0)%, respectively. That causing the decline in broker profits compared to the retailer caused by costs and losses spoiled milk, To the total marketing costs Which caculated for approximately (31%). The results were recommended to using the transfer of milk packed tightly and refrigerated, reduce waste .